Power Situation and renewable energy potentials in Nigeria – A case for integrated multi-generation technology. (November 2021) - Owebor, K.; Diemuodeke, E.O.; Briggs, T.A.; Imran, M.
Abstract: Globally, demand for electricity has seen a steady increase, with nations striving to meet the demand. However, Nigeria is abysmally struggling to meet the increasing demand with the meagre per capita electricity consumption of 151 kWh, which is lower than the average of per capita electricity in Africa. Presently, the grid-tied electricity installed capacity in Nigeria, estimated at 13, 435 MW is primarily generated by fossil and hydro-power plants at approximate distribution of 82.3% and 17.7%, respectively. This work presents single capsule that shows a holistic narrative of the energy access sector in view of energy penetration, sustainability, technology advancement and energy policy evolution. From available records, renewable energy sources in Nigeria are equitably distributed throughout the country, unlike the fossil reserves that are mostly concentrated in the south-south geopolitical zone. Also, there are huge potentials buried within untapped renewable energy in the country, namely wind, small-scale hydropower, geothermal, tidal and biomass energy. Furthermore, cutting edge power generation technologies that incorporate fuel cell, gas-, steam-, and low grade-turbine with carbon capture and fired by dual fuel of natural gas and biomass is promising for both energy access and climate action. The Federal Government of Nigeria's friendly energy policies, coupled with political will to excite implementation are panacea to significantly drive energy access for sustainable socio-economic development. Graphical abstract: Image 1 Highlights: The current electricity generation in Nigeria is relatively poor, and below policy targets. Electricity generation in Nigeria is heavily dominated by high-carbon emission technologies. Nigeria has huge renewable energy potentials to meet the Sustainable Development Goals SDG-7 and SDG-13. Natural gas-biomass (gasified) fuelled low-carbon energy conversion technology with CCS is promising in Nigeria.